Enhancing the Accessibility of Pedestrian Environments: Critical Reflections on the Role of the Public Sector Equality Duty - Anna Lawson; Maria Orchard; Ieva Eskyte; Morgan Campbell (Laws, 2024)
The British Equality Act 2010’s Public Sector Equality Duty (PSED) aims to mainstream equality into the decision-making of public authorities. Although it has generated substantial critique, it has been the subject of surprisingly few empirical investigations, and existing literature does not address the role of the PSED in enhancing accessibility—either in the specific context of streetscapes or more generally. Here, we present the findings of a doctrinal and qualitative study on this topic. It consists of a critical review of relevant case law and an empirical study in which we interviewed disability campaigners, lawyers, and people working in or for public authorities. Two broad issues emerged from the empirical investigation: involvement and enforcement—on each of which our interviewees identified a range of concerns. These, together with our critique of case law, inform our analysis of the impact and effectiveness of the PSED in the context of streetscape accessibility, and accessibility more broadly. We conclude that, while the PSED (together with other Equality Act duties) is charged with a critical role in embedding equality—and, therefore, accessibility—in public authority decision-making, various factors have severely hampered its ability to deliver. Accessibility too often appears to be subordinated to other policy agendas instead of being embedded within them. There is an urgent need for reform to ensure that accessibility is suitably prioritised—both generally and in the particular context of streetscapes.